“Blood” and “Line”: Exploring Kinship Idioms of Nguna, Vanuatu - Facey, Ellen E. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1989)
This paper gives a substantive description of the symbolic aspects of a modern Pacific society’s kinship system. A brief overview of kinship terminology from Nguna, Vanuatu is followed by an exegesis of four key concepts concerning kinship and descent. Ngunese procreation theory is then introduced and compared with material from Ambae, Vanuatu (Poewe and Lovell, 1980; Rodman and Lovell, n.d.) which raises the question of the meaning of Lounsbury’s (1964) classic formal analysis of Crow kinship systems. It is argued that the relationship between the Ngunese idioms of “blood” and “line” is partially explicable in terms of Allen’s (1981) hypothesis that, in numerous and contrasting societies in Vanuatu, the idiom of uterine reproduction gives symbolic form to the conceptualization of not only matrilineal kinship, but other types of kinship as well. Throughout the paper, the more general issue of ethnographic interpretation is addressed.